Developing the Materials of Teaching English as a Foreign Language (TEFL) Subject through Lesson Study - Achmad Hilal Madjdi, Atik Rokhayani; Muh. Syafei (International Journal of Advanced Science and Technology, 2020)
This research aims to develop Teaching English as a Foreign Language (TEFL) material through Lesson Study. This research method is qualitative with the subject of this research being TEFL subject lecturers, collaborative lecturers, and UMK English Education Department students who joined TEFL subjects at the Department of English Language Education at Universitas Muria Kudus. Data was collected using observation sheets and documentation during the learning process. Data analysis starts with data reduction, data presentation, and data verification on qualitative data analysis. The results show that through the Lesson Study approach teachers can engage in professional development that leads to activities encouraging learning change. Lesson study can be implemented not only to have a better teaching and learning process but also to develop the subject matter being taught. The procedure for developing this subject matter is in line with the learning stages of the lesson, namely Planning, Conducting, Finding, and Reflecting.